(untitled) (Global Journal of Human-Social Science, 2026)
Comparative research applying the genetic-critical method with which Ludwig Feuerbach (1804-1872) analysed Catholicism (1841) and Protestantism (1844), among other religions not yet addressed by Feuerbach. For this purpose, the author examines other religions that are currently global: Vedic (or Brahmanic), Orthodox (Christian), Jewish (Hebrew), Muslim (Islamic), Buddhist, Spiritist (Kardecist), traditional African or diasporic, Taoist, Jainist, Confucian, Mormon, Shintoist, Wiccan, and Masonic (whose religious characteristic is postulated, despite being denied by the institution). Each of these is considered an intangible cultural heritage through which human identity has been historically objectified and can be assumed contemporaneously as they are interpreted according to Feuerbach’s proposal. Exposing their humanistic and naturalistic vocations contributes to humanity becoming a future community of planetary destiny, because it is rooted in its identity diversity and preferential partnerships with nature in its historical development as we advance.